Quality of Schooling, Returns to Schooling and the 1981 Vouchers Reform in Chile - Patrinos, Harry Anthony; Sakellariou, Chris (World Bank, Washington, DC, 2012)
This paper exploits unique information on cognitive ability to examine the importance of schooling and non-schooling cognitive skills for heterogeneous individuals using instrumental variables estimation. Using a binary instrument based on the 1981 reform in Chile, the authors find that the main beneficiaries of the reform were those who at the time were pupils in basic schooling (ages 6-13). For this treated group of pupils, only a negligible part of the estimated return to schooling is due to classical ability bias. The labor market reward to an additional year of schooling is a measure of the "true" non-cognitive return to schooling. However, once the treated group is expanded to include secondary school students, the pure return to schooling decreases dramatically, while the return to schooling cognitive and non-schooling cognitive skills increases accordingly, suggesting that a large part of the estimated return in an earnings function is due to classical ability bias. For this treated group (mixture of basic school and secondary school age students), the labor market rewarded cognitive skills (especially those acquired through schooling) significantly.